Implementation Of Activity Based Costing System In Making Affort To Determine The Tariff Of Operation Action (Case Study In Surabaya Royal Hospital) - Kustiningsih, Nanik; Atmadja, Soesilawati Soema; Patmana, Ois (Archives of Business Research, 2017)
The purpose of this study is to determine whether the application of activity-based costing system can show a more accurate resource allocation at Royal Hospital Surabaya . As well as a comparison tool with operating rates that has been established so far, especially in its application to a hospital that its orientation two goals that is community service and profit balance. This research was conducted at Royal Hospital Surabaya. The method used is descriptive method that is calculate the tariff of hospital operation action at this time, set cost method based on activity based costing, then compare tariff of operation action based on activity based costing with its realization. The results showed that from the calculation of the tariff of the operational action by using activity-based costing, if it is compared with the tariff used by the hospital, activity-based costing gives greater results for small operation actions and gives smaller results for medium and large operations. This is due to the overhead cost of each product. In activity-based costing, the overhead cost of each product is charged to many cost of drivers. So in activity-based costing, has been able to allocate the cost of activity to each operational action based on the consumption of each activity